Efek Anti Inflamasi Enzim Bromelin Nanas Terhadap Osteoartritis - Andini Bakti Putri; Anita Anita (Politeknik Kesehatan Tanjung Karang, 2017)
Inflammation is a complex reaction of the body's immune system in the vascular tissue that causes the accumulation and activation of leukocytes and plasma proteins that occur during infection, poisoning or cell damage. Inflammation can be treated by using anti-inflammatory drugs such as NSAIDs (Non-Steroidal Anti-Inflammatory Drugs) that serve as pain reliever, febrifuge, and anti-inflammatory. One of the most common chronic inflammatory diseases is osteoarthritis. Osteoarthritis is the most common form of arthritis in society,which has a major impact on public health problems. Currently there are many therapeutic modalities of both pharmacology and non-pharmacology for the management of osteoarthritis, therefore it is necessary to recommend effective treatment of osteoarthritis in Indonesia based on the latest scientific evidence. The use of NSAIDs that do not correspond to doses can cause side effects such as bleeding, gastric ulcers, worsening asthma symptoms and acute kidney failure. This is the health problem in Indonesia, especially for ordinary people who use NSAIDs with excessive doses, because they want to quickly relieve pain. Therefore, it is necessary to look for a safe anti-inflammatory drug and can reduce the pain caused to arthritis. Ananascomosus (pineapple) has long been used for various medical purposes. There are four different proteases in the pineapple, the two major enzymes in pineapple defined as bromelain’s stems and bromelain’s fruit. In the latest study there are various therapeutic benefits that have been proposed for bromelin, such as anti-inflammatory, reducing swelling, reducing pain, facilitating the digestive system, accelerating wound healing and acting as an anticoagulant.